Modelo de compartilhamento de localização em redes sociais móveis com garantias de privacidade - Rosa, Tiago Antônio (Universidade Federal de São Carlos, 2015)
Mobile social networks are characterized by the sharing of user context information, such as the location of one’s mobile device, with one’s friends and groups of friends. The location information in a social network enables providers to offer products and services based on geographical area, which is considered either a personal gain or an invasion of privacy by the users who receive these offers. A user sharing location information with a particular friend or group of friends, without social network providers having access to this information, ensures the safety and privacy of the information. This paper presents a model of mobile social networking with privacy guarantees regarding sharing the location of members with groups of friends; it allows users to configure rules that determine to whom, when and where location information can be made available. The model provides three levels of privacy, chosen by the user, using techniques of anonymity and diffusion, which adjust the location to ensure the concealment of the information before it is made available on the social network. The proof of concept of the proposed model, called RSM Privacy, was developed for the Android platform. Performance tests showed that delays generated by the use of RSM Privacy are proportional to and justifiable for the privacy levels desired and chosen by users. A group of 50 users evaluated the model proof of concept, RSMPrivacy, with respect to usability and verified the efficiency of the techniques included in the proposed model.
Keywords: Redes Sociais Móveis; Privacidade; Compartilhamento de Localização; Mobile Social Network; Privacy; Location-sharing; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO